Selective mono-N-methylation of aniline substrates on Cu1-xZnxFe2O4 - Vijayaraj, Munusamy; Gopinath, Chinnakonda S. (Applied Catalysis A-General, 2007)
Selective mono-N-methylation of substituted anilines (o-, m- and p-toluidines, 2,6-xylidine, p-anisidine and p-aminoacetophenone) was carried out with methanol as methylating agent under vapor phase reaction conditions on Cu1-xZnxFe2O4 systems. The catalytic reactions with each aniline substrate were carried out at optimum reaction conditions (MeOH:anilines:water = 3: 1: 1, space velocity = 3.58 h(-1)) between 543 and 603 K. The presence of a ring-directing group did not have any significant influence on the N-methylaniline(s) selectivity, which remains very high; the same initial conversion/yield was observed for at least 11 h. Electronic effects due to different groups in the above aniline substrates influence the reactivity of the substrates in terms of conversion and yield. Toluidine reactivity varies with respect to the position (ortho, meta and para) of the methyl group on the phenyl ring. Para-substituted anilines (p-toluidine and p-anisidine) exhibit comparable catalytic activity, while p-aminoacetophenone shows higher conversion. The perpendicular orientation of toluidine substrates on catalyst surfaces influences the conversion and N-methyltoluidine yield. Increased crowding at ortho-position and hence steric hindrance (aniline > o-toluidine > 2,6-xylidine) restrict the substrates interaction with the catalyst surface, and 2,6-xylidine shows no reactivity. The best catalytic activity observed with Cu0.5Zn0.5Fe2O4 was due to a heterogeneous distribution of metal ions on the surface with Zn serving as active spacer group as well as methyl species source. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: mono-N-methylation; N-methylaniline; N-methylation; selective N-methvlation; spinel